Lactobacillus rhamnosus GG mitigates bone loss induced by mechanical unloading via regulation of the gut-bone axis - Qin, Xuezhi; Lian, Yu-E; Tang, Hanqin; Chai, Xin; Gao, Yuhai; Ma, Yanchun; Guo, Jing; Wang, Hongli; Wang, Yan; Wang, Biaomeng; Chen, Jiayu; Wang, Yixuan (Frontiers in Nutrition, 2026)
BackgroundBone loss is a serious complication of mechanical unloading, such as that experienced during spaceflight or prolonged bed rest, and represents a significant clinical concern. Although the gut-bone axis has been implicated in bone homeostasis, its role under unloading conditions remains underexplored.MethodsIn this study, we employed a hindlimb unloading (HU) mouse model to investigate the underlying mechanisms of HU-induced bone loss and the potential protective role of Lactobacillus rhamnosus GG (LGG). Gut microbiota (16S rRNA sequencing), short-chain fatty acids (LC–MS/MS), intestinal barrier proteins (ZO-1/Occludin), inflammatory cytokines in bone tissue (TNF-α/IL-1β/IL-10), regulatory T (Treg), bone markers (BALP/OPG/OCN/PINP/CTX), and microarchitecture (Micro-CT) were analyzed.ResultsHindlimb unloading (HU) disrupted gut microbiota composition, reduced short-chain fatty acids (SCFA)-producing bacteria, and decreased SCFA levels, which was accompanied by reduced expression of ZO-1 and Occludin, elevated circulating LPS levels, and enhanced inflammatory markers in the bone microenvironment. Additionally, the proportion of Treg cells was reduced, which was associated with markers indicative of disrupted bone remodeling. LGG treatment was associated with partial restoration of microbial composition and SCFA levels, accompanied by improved intestinal barrier markers, reduced LPS and inflammatory cytokines, increased Treg proportions, and amelioration of bone microarchitecture.ConclusionThese findings suggested that LGG may have conferred protection against unloading-induced bone loss, potentially through modulation of the gut microbiota, alterations in SCFA profiles, improvement of intestinal barrier function, and immune regulatory changes involving Treg cells. This work highlighted the therapeutic potential of targeting the gut-bone axis to mitigate bone loss in microgravity or immobilization settings.